The strategic traits of overseas Chinese in Southeast Asia: a case study of selected prominent businessmen / Yeop Hussin Bidin - Bidin, Yeop Hussin (2011)
The Australian Department of Foreign Affairs and Trade in 2006 reported that the Overseas Chinese constitutes fewer than 10 per cent of the population of ASEAN, but they make up 86% of the billionaires in the region. They generated also an estimated GDP equivalent of about US$450 billion, almost at par with China GDP ofapprox US$500 billion The Overseas Chinese have influenced the nature of economic prosperity in Southeast Asia by actively contributing to the vast spectrum of business interest from the more traditional agricultural to the latest adventure in the information and communication technology. They had pioneered some of the established global brands such as Red Bull - energy drink; Top Glove-rubber pharmaceutical products; Shangri-La hotel chain, Winston cigarette and SM Retail Chain. The culture and traits inherited from the early years of immigration and their eventual assimilation into the mainstream Southeast Asian population which is dominated by the Indochinese and Malay ethnics reflect the dynamism and courage of these settlers to chart the future of their next generation and subsequently that shaped the economic landscape of this present region. The strategic traits of the five prominent businessmen attributed clanship and their emphasis on trust, clan loyalty and enforcement as the guiding principles in sustaining Overseas Chinese business in Southeast Asia, and hence their perseverance and commitment in the conduct of their business.